Réponses

  • Utilisateur Brainly
2014-09-11T22:10:52+02:00
E= 3(x - 1) + (1 - x)(x + 1) 
E= (x - 1)(3 + 1 - x)
E= (x - 1)(4 - x)

F= (2x + 3)² - (2x + 3)
F= (2x + 3)(2x + 3 - 1)
F= (2x + 3)(2x + 2)
Merci beaucoup :)
De rien! =)
Bonsoir Jordan mais peut-être une petite erreur de frappe 3(x-1)+(1-x)(x+1) = 3(x-1)-(-1+x)(x+1) = (x-1)(3 - x - 1 ) = (x-1)(2 - x)
2014-09-11T22:16:40+02:00


Bonsoir

Factorisons

E = 3(x - 1) + (1 - x)(x + 1) 

E = 3(x-1) - (x-1)(x+1)

E = (x-1)[3-(x+1)]
E = (x - 1)(3 - x + 1)
E = (x - 1)(4 - x)

F= (2x + 3)² - (2x + 3)

F = (2x + 3)(2x+3) - (2x + 3)

F = (2x + 3)[(2x + 3) - 1]
F= (2x + 3)(2x + 3 - 1)
F= (2x + 3)(2x + 2)